2003
DOI: 10.1149/1.1560638
|View full text |Cite
|
Sign up to set email alerts
|

A Statistics-Based Approach to Studying Aluminum Pit Initiation

Abstract: A statistical description of pit initiation in high-purity aluminum ͑99.99͒ is developed based on the statistical frameworks established by Baroux ͓Corros. Sci., 28, 969 ͑1988͔͒ and Shibata and Takeyama ͓Corrosion, 33, 243 ͑1977͒ and 52, 813 ͑1996͔͒. The statistical treatment is used to examine the dependency of pitting behavior on electrode area, scan rate, and chloride concentration. It is shown that the average pitting potential is proportional to the log of the scan rate and the log of one over electrode a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The results in Figure 9 provide the foundation for a possible tradeoff in the corrosion resistance of partially devitrified glasses based on precipitate radius. The probability of pit nucleation at a nanocrystal might increase with an increase in its size, [34] but, because the surrounding amorphous matrix collects the beneficial solutes, it becomes more difficult for that pit to propagate beyond the precipitate and into the amorphous matrix. [32] However, the decrease in the distance of separation between the precipitates with an increasing precipitate radius means that less amorphous matrix would need to be penetrated for the pitting attack to reach another susceptible precipitate.…”
Section: Resultsmentioning
confidence: 99%
“…The results in Figure 9 provide the foundation for a possible tradeoff in the corrosion resistance of partially devitrified glasses based on precipitate radius. The probability of pit nucleation at a nanocrystal might increase with an increase in its size, [34] but, because the surrounding amorphous matrix collects the beneficial solutes, it becomes more difficult for that pit to propagate beyond the precipitate and into the amorphous matrix. [32] However, the decrease in the distance of separation between the precipitates with an increasing precipitate radius means that less amorphous matrix would need to be penetrated for the pitting attack to reach another susceptible precipitate.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of electrode area on the extent of ennoblement observed in pitting potential measurements can be understood in the context of arguments presented by Wall and Martinez [20], who distinguish homogeneous and heterogeneous forms of pit initiation. According to their arguments, heterogeneous pit initiation refers to pitting at specific sites that possess a high probability of pitting.…”
Section: The Effect Of Cu On Pitting Potential Ennoblementmentioning
confidence: 94%
“…Generally, as electrode area is decreased, the measured pitting potential increases, all other factors being equal [20]. This behavior is attributed to the idea that the probability of an electrode containing a particularly weak site that initiates pitting at low potentials decreases as the exposed area decreases.…”
Section: Area Effectsmentioning
confidence: 99%
“…Recently, we reviewed the derivation of such a model; the details can be found elsewhere. 3 Here we briefly summarize the equations necessary to calculate the pitting potential distribution from parameters that can be extracted from induction time data.In the mid-1970s, Shibata developed a statistical treatment of pit nucleation in stainless steel which expressed both E pit and in terms of a germination rate, ͑s Ϫ1 ͒. 4 More recently, we applied this treatment to the pitting behavior of aluminum and found that could best be described by an exponential dependence on potential 3…”
mentioning
confidence: 99%